PROCESSING USED COOKING OIL INTO SOAP AS AN EFFORT TO ESTABLISH HOME INDUSTRY - Tri Murwaningsih (Universitas Ahmad Dahlan, 2021)
Cooking oil is a daily necessity used by a family for cooking purposes. As the consumption level of cooking oil increases, it turns out slowly producing waste in the form of used cooking oil. The purpose of this research is to provide training in processing used cooking oil into soap. The training method in the research carried out several stages including preparation, socialization, soap production process, follow-up and evaluation. The training was held in Bulu, Jaten Village, Karanganyar Regency, ob January 16, 2021. The soap was processed from used cooking oil in various stages and mixed with chemicals in approximately 1 month. The results of the training activities could innovate the productivity of the local community with long-term prospects to welcome the empowerment of economically independent of Dusun Bulu residents. It can also build a Home Industry to increase the use-value of used cooking oil